Physical education of students, considering their physical fitness level - A.S. Andres (Physical Education of Students, 2017)
Purpose: to determine effectiveness of students’ physical education program, mainly directed at development of leading physical qualities. Material: 100 students participated in experiment. In control group (n=50) all physical qualities were trained equally. In experimental group (n=50) loads were directed at training of leading (better trained) physical qualities. Results: we detected higher physical culture-sport activity of students in conditions of the author’s program’s application. Higher health related effectiveness of experimental program was illustrated also by its facilitating increasing the students’ weekly activity. The found facts prove effectiveness and importance of those physical loads’ priority application in trainings process, to which students have genetic bent. Conclusions: demand and timeliness of individual-typological approach is conditioned by the following: distinctions in students’ physical fitness; personalities’ specificities of students’ reactions to external factors and physical loads.